Trouble at Work - Fevre, Ralph (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Trouble in the workplace - whether it is bullying, harassment or stress - is always in the headlines. Yet, in many discussions, the research and statistics that are cited prove unreliable. This book summarizes the largest specialist research programme on ill-treatment in the workplace so far undertaken. It provides a powerful antidote to half-truths and misinformation and offers a new way of conceptualizing trouble at work, moving the discussion away from individualized explanations - and talk of 'bullies' and 'victims' - towards the workplace characteristics that cause trouble at work. The biggest problems arise where organisations fail to create a workplace culture in which individuals really matter. Paradoxically, these are often the organizations which are well-versed in modern management practices.